Ky. Acts 327 - (:unkn) unknown (My University, 1874)
An Act to Revise and Amend the Charter of the City of Newport,§6: Prohibited the manufacture of gunpowder or other explosive, dangerous, or noxious compounds or substances within the city
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER